2018
DOI: 10.15585/mmwr.mm6722a1
|View full text |Cite
|
Sign up to set email alerts
|

Vital Signs:Trends in State Suicide Rates — United States, 1999–2016 and Circumstances Contributing to Suicide — 27 States, 2015

Abstract: IntroductionSuicide rates in the United States have risen nearly 30% since 1999, and mental health conditions are one of several factors contributing to suicide. Examining state-level trends in suicide and the multiple circumstances contributing to it can inform comprehensive state suicide prevention planning.MethodsTrends in age-adjusted suicide rates among persons aged ≥10 years, by state and sex, across six consecutive 3-year periods (1999–2016), were assessed using data from the National Vital Statistics S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
381
1
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 571 publications
(400 citation statements)
references
References 8 publications
10
381
1
8
Order By: Relevance
“…Although treatment for mental health problems is an essential component of suicide prevention, previous research with NVDRS data has documented that more than half of suicide decedents did not have a known mental health condition ( 21 ). That study indicated that multiple factors contribute to suicide among those with and without known mental health conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although treatment for mental health problems is an essential component of suicide prevention, previous research with NVDRS data has documented that more than half of suicide decedents did not have a known mental health condition ( 21 ). That study indicated that multiple factors contribute to suicide among those with and without known mental health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol use is a robust predictor of suicidal behavior ( 32 ), victimization ( 33 ), and interpersonal violence perpetration ( 17 , 27 ). Intoxication can lead to disinhibition, enhance feelings of hopelessness and depression, and impair judgment that can lead to impulsive behaviors ( 21 ). Alcohol use can also reduce awareness and perception of surrounding risks, thus increasing one’s vulnerability to being victimized ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Suicide is a leading cause of death worldwide, and the 10th leading cause of death in the USA (Centers for Disease Control and Prevention, ). Despite increased public attention and ongoing research efforts in suicide prevention, in the USA suicide rates increased by 30% between 1999 and 2016 (Stone et al, ), with nearly 45,000 deaths by suicide in 2016 (Centers for Disease Control and Prevention, ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, while conscious suicidal ideation may or may not precede suicide, only a minority of suicide decedents reveal it through self‐report. A recent Centers for Disease Control and Prevention (CDC) report underscored that self‐reported suicidal ideation was present only in a fraction of suicide decedents (Stone et al, ). Of those who died by suicide and had a diagnosed mental health condition, 24.5% expressed suicidal intent.…”
Section: Introductionmentioning
confidence: 99%
“…For example, three US‐based studies included in a recent meta‐analysis suggested lower prevalence of depression among rural versus urban older adults . However, other recent US studies have revealed increasing rates of suicide and alcohol‐related and drug‐related deaths in rural and sparsely populated regions, suggesting that mental health outcomes may disproportionately burden these areas. Our results add to this growing literature on geographic health disparities by suggesting that the prevalence of elevated depressive symptoms may be higher among participants who lived in the rural United States during childhood.…”
Section: Discussionmentioning
confidence: 99%